Factors associated with the use of dental services in diabetic people - Ortega, Andrea Patricia Ramirez; Vera-Ponce, Victor Juan; Ortega, Leslie Espinosa; De La Cruz-Vargas, Jhony A. (Intelektual Pustaka Media Utama, 2024)
The use of dental services prevents oral diseases where its prevalence is associated with chronic diseases such as diabetes mellitus (DM) that also has increased risks with age. Therefore, this observational, analytical and crosssectional study was conducted among 3,882 people. Data used for analysis in this research was collected from the Demographic and Family Health Survey of Peru (ENDES) from 2019 to 2021. Results from poisson regression analysis showed female gender had 1.02 times the probability of going to the dental service; likewise, people who were 91 to 100 years old had 12% more, the probability, like those with secondary education, had 8% more and those with the highest average, richest and richest wealth index had 20% more, 29% more and 29% more, respectively, the probability of going to the dental health service, as opposed to those who were very poor. The study concluded that there are several sociodemographic factors (such as being female, age progressed, natural region, those with high school, wealth index, type of residence) and personal factors (history of hypertension (HTN), physical disability) associated with a lack of access to dental services in people over 60 years old.